Pengaruh Kafein Terhadap Lengkung Ekor Spermatozoa Epididimis Sapi Bali - Oktora Dwi Putranti (Fakultas Pertanian Universitas Veteran Bangun Nusantara Sukoharjo, 2018)
This study aims to analyze the influence of caffeine on the distance of the tail movement of the spermatozoa epididymis cattle Bali. Methods in this study with a collection of sperm from Slaughter House (RPH) and then conducted the process of freezing with Tris yolk dilution. Treatment of caffeine with levels of 0 mg/ml, 2 mg/ml, 4 mg/ml and 6 mg/ml in spermatozoa that have been in thawing. The variables observed were DCL, DAP, DSL, ALH analyzed by CASA. Results showed no difference (P> 0.05) motility with caffeine treatment and short sperm tailwave distance of 37.27 μm showed the sperm motility velocity. Keywords: spermatozoa tail, caffeine